Accessory Nipple on the Sole of Foot: A Case Report (Jalalabad Medical Journal, 2026)
This case report presents a rare occurrence of an accessory nipple on the sole of a 7-month-old female patient's right foot. The patient was presented with a well-formed nipple surrounded by areola, measuring 2.5×2.5 cm in diameter. Following surgical excision, histopathological examination confirmed the absence of glandular tissue. This case is classified within the fifth category according to Kajava's classification, signifying the presence of nipple and areola without glandular tissue. The report discusses the clinical presentation, diagnostic assessment, and implications of foot accessory nipples, emphasising the importance of informed consent and awareness of potential changes in such cases.Jalalabad Med J 2025; 22 (2): 89-91